A unique three-layer full adder in quantum-dot cellular automata. (September 2020) - Heikalabad, Saeed Rasouli; Salimzadeh, Fereshteh; Barughi, Yashar Zirak
Highlights: An overview about basic features of QCA is presented. The elementary components of QCA circuits are explained. A new structure for single-bit full adder is designed using the three-input XOR gate and three-input majority gate in three-layer. Simulation results of the proposed structure are verified using QCADesigner version 2.0.3. Abstract: Unlike previous technologies, QCA does not depend on the movement of electrons in the wire to transmit information. This feature significantly improves the speed of the circuits and reduces the power consumption, which is a great incentive for digital circuit designers to use this technology. In this paper, a new structure of full-adder is proposed, designed, implemented and simulated using two gates that improve the complexity and latency compared to previous designs. Simulation results are obtained using QCADesigner which illustrates the valid performance of the proposed design. The proposed structure has a 30% improvement in the number of cells and a 41% improvement in the occupied area. Graphical abstract: Image, graphical abstract